Genetic Information to Share with Parents when Newborn Screening Reveals the Presence of Sickle Cell Trait - Narcisse Elenga (Hindawi Limited, 2024)
The primary purpose of newborn screening for sickle cell disease is to diagnose the disease before the appearance of symptoms and to initiate early treatment. To answer the question "What genetic information needs to be communicated to parents when newborn screening reveals the presence of a sickle cell trait," we conducted a survey using a self-administered online questionnaire. We received responses from 122 healthcare workers and members of sickle cell disease associations, in France and French overseas departments. Our results showed similar positions on this issue. The information conveyed is not consistent and is the result of grassroots initiatives. The negative consequences generated by this information could be reduced when this information is delivered by a multidisciplinary team, within the framework of a dedicated consultation. This information on sickle cell trait status should be given in at least three key periods: the neonatal period, early adolescence, and later adolescence, when reproductive implications become important. Neonatal screening programs should develop systems that allow referring physicians to easily access the results of neonatal screening electronically. Harmonization of practices should allow a better analysis of the consequences of this counselling on family projects.